South-South Technical Knowledge Exchange and Learning Initiative (STEKELI) Workshop - Amha, Yosef; Demissie, Teferi Dejene; Makonnen, Brook T.; Zougmoré, Robert B.; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
In Africa, many actors, programmes, projects, or initiatives are implemented by international organizations or continental institutions, or sub-regional and national entities to improve the development, provision, uptake and use of weather and climate services1 .For instance, the Regional Climate Centers (RCCs) have been engaged in developing models and methodologies based on ground and satellite observations to forecast/monitor rainfall, cropwater requirements, drought, early warning system, weather/climate, and seasonal and inter-annual variations. They have also provided training in a wide range of expertise in agro-meteorology, hydrology, and equipment maintenance, as well as on topics related to food security, climate change, and sustainable natural resources (land and water) management. Reliable observed climate data are essential to monitoring past and current weather and climate conditions, producing reliable forecast information, assessing the models' skill, understanding climate variability and longterm changes, and assessing sectoral impacts (agriculture, water resources, and health). Reliable climate information could, therefore, help build resilience against the negative impact of climate change and improve people's livelihood.